Factors influencing adoption of Napier grass in smallholder dairying in the highlands of Kenya - Irungu, P.; Mbogoh, S.G.; Staal, Steven J.; Thorpe, W.R.; Njubi, D. (British Society of Animal Science, 1998)
Smallholder dairying in Kenya is mainly concentrated in the central and western parts of the country, where the highland climate and proximity to urban markets are favourable. These farmers produce over 70 percent of the total marketed milk (Omiti et al., 1993), using an average of two cows (mostly Bos taurus) on about one ha. of land (Omore et al., 1997). Milk productivity on smallholder dairy farms is usually low due to poor nutrition, disease and uncoordinated breeding (Omore, 1996). Planting forages may improve the level of feeding and nutrition and thus raise both farm productivity and the overall supply of milk to growing urban markets. This study quantitatively evaluated factors that influence the adoption of Napier grass (Pennisetum purpureum) as a planted forage in Kiambu District, with a view to understanding the mechanisms of adoption of planted forages. The cultivation of Napier grass is carried out by some 70 percent of Kiambu dairy farmers (Staal et al., 1997). This high rate of adoption allows the close examination of the factors influencing the probability and degree of planted fodder adoption, both jointly and independently. This understanding could assist efforts to promote planted fodder in other areas of highland Kenya, whether Napier or other species such as herbaceous legumes.